VILLAGE-OWNED ENTERPRISE MANAGEMENT AND RURAL ECONOMIC INDEPENDENCE IN TABORE - Sri Andayani; Nihayatus Sholichah; Ika Devy Pramudiana (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes the effectiveness of Tabore Maju Bersama Village-Owned Enterprise (BUMDes) management and its contribution to the economic independence of Tabore Village, Mantangai District, Kapuas Regency, Central Kalimantan. A descriptive qualitative case-study design was used. Data were collected through in-depth interviews, observation, and documentation involving six informants: the village head, BUMDes director, treasurer, Village Consultative Body chair, district community-empowerment officer, and a community leader. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while validity was established through source and technique triangulation. Duncan’s organizational-effectiveness framework—goal achievement, integration, and adaptation—and Friedmann’s community-empowerment perspective guided the analysis. The findings indicate that BUMDes management is moderately effective, although integration and adaptation remain weak. Village-generated revenue increased by 85.3% between 2021 and 2024, but fiscal dependence on central Village Funds remains high. Business diversification is limited, financial governance is not standardized, and community participation is largely passive. The study recommends standardized operating procedures, structured managerial training, improved transparency and participation, digital financial records, and more intensive district and regency-level assistance adapted to remote-area conditions.